Pengaruh Ukuran Perusahaan, Kebijakan Utang dan Risiko Bisnis terhadap Nilai Perusahaan - Umayah, Umayah; Ratnasari, Fina (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the influence of firm size, debt policy, and business risk on firm value in the food and beverage subsector of consumer non-cyclicals listed on the Indonesia Stock Exchange. The research is motivated by fluctuating financial performance and investor concerns regarding external shocks such as rising raw material costs and currency exchange losses. Using a quantitative associative method, the study employs secondary data from 33 companies observed over the 2019–2023 period. Data were analyzed with panel data regression using EViews 12, supported by descriptive statistics and classical assumption tests. The findings reveal that firm size and debt policy significantly affect firm value, while business risk shows no significant effect. Moreover, the three variables jointly demonstrate a substantial influence on firm value, with firm size and debt policy emerging as the dominant factors. These results highlight the importance of optimal debt management and corporate scale in strengthening firm value and maintaining investor confidence, particularly in industries facing dynamic external conditions.